OCEANIC LITHOSPHERE 2. The Origin and Evolution of Oceanic Lithosphere: Bathymetry and Morphology of the Ocean Basins - Malpas, John; Robinson, Paul (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1998)
Summary The development of high-precision surveying instruments over the last 30years has made possible the systematic mapping of the ocean basins, completely changing our view of the seafloor. What was once thought to be a featureless plain covered with sedimentis now known to contain a variety of complex and intricate structures. Unlike terrestrial surfaces, which owe their shape largely to erosion, the sea floor preserves a much more continuous record of the volcanic and tectonic processes by which it was formed. The ocean basins are divided broadly into continental margins, abyssal depths, and mid-ocean ridges. Passive margins, such as those surrounding most of the Atlantic Ocean, typically have broad continental shelves underlain by great thicknesses of sedimentary rock, whereas active margins have narrow shelves and are characterized by subduction zones and volcanic arcs. Ocean basins adjacent to passive margins typically have flat abyssal plains underlain by turbidites, whereas those adjacent to active margins typically have a more irregular bathymetry broken by numerous abyssal hills. The morphology ofthe world-encircling mid-ocean ridges varies with spreading rate, and reveals a pattern of segmentation closely linked to the volcanic and tectonic processes associated with sea-floor spreading.